Soluções de buracos de minhoca percorríveis gerados pela energia de Casimir - Oliveira, Pedro Henrique Ferreira de (2024)
Wormholes (WH) require negative energy and thus an exotic matter source. Because Casimir energy is negative, it has long been speculated as a good candidate source for these objects. However, only very recently a complete solution for D = 4 was found by Garattini (2019), indicating that Casimir energy can be a source of traversable WHs. Shortly thereafter, Alencar, Bezerra and Muniz (2021) showed that this is not true in D = 3. In this thesis, we demonstrate that Casimir energy can be a source of Morris-Thorne type wormholes for all spacetimes with D > 3. Additionally, by introducing the cosmological constant, we find that for D = 3, Casimir WHs are possible but the spacetime must always be AdS. For D > 3, we show that the cosmological constant reverses sign with increasing throat size. Finally, we outline a more consistent way to generalize Casimir wormholes through Yukawa-type corrections, revealing criteria for constraints on their parameters and the possibility of a broader category of astrophysical objects, such as slightly repulsive wormholes.